The effect of bivalent HPV vaccination against invasive cervical cancer and cervical intraepithelial neoplasia grade 3 (CIN3+) in the Netherlands: a population-based linkage studyResearch in context - Marit Middeldorp; Jesca G.M. Brouwer; Janneke W. Duijster; Mirjam J. Knol; Folkert J. van Kemenade; Albert G. Siebers; Johannes Berkhof; Hester E. de Melker (The Lancet Regional Health. Europe)
Summary: Background: The protective effect of HPV vaccination against cervical cancer has been demonstrated in registry linkage studies. The start age of screening in those studies was lower than 25 years. We aimed to estimate the effectiveness of bivalent HPV16/18 vaccination against invasive cervical cancer and cervical intraepithelial neoplasia grade 3 (CIN3+) in the Netherlands, where routine screening starts at age 30 years. Methods: We linked the vaccination status of women born in 1993 who were eligible for HPV vaccination at age 16 years with histopathological results recorded until April 1, 2024, in the nationwide pathology databank (Palga). Cumulative risks of invasive cervical cancer and CIN3+ were estimated for fully vaccinated (3 doses or 2 doses ≥150 days apart), partially vaccinated, and unvaccinated women. Cumulative risk ratios (CRRs) were adjusted for differences in screening participation between vaccine groups. Findings: A total of 103,059 women were included, of whom 47,130 were fully vaccinated, 5098 partially vaccinated, and 50,831 unvaccinated. Five cancers (0·011%) were observed in fully vaccinated, two (0·039%) in partially vaccinated, and 42 (0·083%) in unvaccinated women. The CRR for fully vaccinated women compared with unvaccinated women was 0·085 (95% confidence interval 0·025, 0·24) for cancer and 0·19 (0·16, 0·23) for CIN3+. The CRR for partially vaccinated women was 0·52 (0·12, 1·71) for cancer and 0·42 (0·30, 0·57) for CIN3+. Interpretation: The risk of cervical cancer and CIN3+ was strongly reduced in vaccinated women indicating that vaccine protection extends at least until age 30. Funding: The Dutch Ministry of Health, Welfare, and Sport.